PENGENALAN DASAR INVESTASI BAGI IBU RUMAH TANGGA SERTA PELAKU UMKM DALAM KOMUNITAS “MAK PINTAR” - Deasy Ariyanti Rahayuningsih; Aan Marlinah; Erika Jimena Arylin; Emir Kharismar; Novia Wijaya (Bajang Institute, 2025)
The aim of the training is to provide basic information about financial investment to prospective novice investors which are housewives and also small medium business actors. They are incorporated as the member of community empowerment for women “Mak Pintar”. The training was held at the PT. Eden Kreasi Indonesia office, Alam Sutera, South Tangerang on March 20, 2024 which were attended by 10 participants and 6 Trisakti School of Management’s lecturers as facilitator. The 10 young mothers as prospective novice investors were introduced about the various financial investment instruments in Indonesia. The training’s benefit for participants were expected not only be wise and knowledgeable in managing their household living expenses but also smart in allocating the financial funds for education savings, stocks and mutual funds in the future. The participants were expected not only become a smart in handling the investment instruments and financial’s decision making but also being able to meet their daily household needs, creating the welfare family and reaching the better life.